EVALUASI IMPLEMENTASI KURIKULUM MATA PELAJARAN PRODUKTIF SMK NEGERI 1 SAMARINDA - Ramli, Akhmad (CENDIKIA, 2021)
This study aimed to evaluate the general program implementation curriculum subjects productive trip business skills program in SMK Negeri 1 Samarinda. This study used a qualitative approach. Collecting data using (1) interviews, (2) observations (3) documentation, and (4) Questionnaires. Analysis of data using four components, namely data collection, data reduction, data presentation and conclusion. The results showed (1) The evaluation of the program in the context of components that include requirements analysis, vision, mission, goals and curriculum schools of business expertise trip to the category of "Very Good. (2) The evaluation component inputs that include aspects of teachers and management, student management, infrastructure management, financial management and management education calendar. the category of "Very Good" (3) The results of the evaluation component of the learning process that includes planning, implementation of the process of learning, assessment, and monitoring of the learning process with the category of "Very Good". (4) The results of the evaluation component of output that includes the results of the theory of productive subjects of national examinations, the results of practical subjects and the results of national examinations productive work practices Industries (prakerin) and absorption graduates with the category of "very good"